Relevant Cost Analysis for Special Order Decisions to Increase Profits at Wingko Babat Lamongan - Dewianawati, Dwi; Negoro, Anis Sirojuddin Suryo; Indrianto, Dian; Puspitasari, Novrina (PT FORMOSA CENDEKIA GLOBAL, 2024)
The problem in this research is the application of the relevant costs on companies Wingko in decisions to accept or reject the special order to increase profits. The purpose of this study is to find out about the appropriate cost calculation made by the company to accept or reject special orders as well as to analyze the relevant costs about decisions on accepting or rejecting special orders. The method used is quantitative descriptive. The results showed that the company is still not appropriate in analyzing the use of the relevant costs. The analysis of special orders in 2017 from Mr. Ali, 2018 from Mr. Hasan, 2019 from Mrs. Ida, 2020 from Pondok yayasan Iman, and Mrs. Siti, and the last in 2021 of Mrs. Rini and Mrs. Ika is acceptable. So that the company's profit would increase from special orders are accepted